Mesostructured g-C3N4 nanosheets interconnected with V2O5 nanobelts as electrode for coin-cell-type-asymmetric supercapacitor device. (September 2021) - Devarayapalli, K.C.; Lee, K.; Do, H.-B.; Dang, N.N.; Yoo, K.; Shim, J.; Prabhakar Vattikuti, S.V.
Abstract: In this study, low-cost, noble-metal-free, ecologically friendly, high-performance coin-cell-type supercapacitors are constructed using an efficient one-pot approach. Two novel nanostructures comprising V2 O5 nanobelts—one with and one without cetyltrimethylammonium bromide (CTAB)-modified g-C3 N4 —are synthesized via a hydrothermal process (g-C3 N4 nanosheet (CN)/VO and CTAB-modified pore-rich g-C3 N4 nanosheet [CCN]/VO nanostructures, respectively). CTAB is used as a sacrificial template to generate mesoporous structures in the g-C3 N4 nanosheets. The CCN/VO nanostructure exhibits a larger surface area (73.5 m 2 /g) than that of CN/VO (54.1 m 2 /g) and superior specific capacity (192.3 mAh/g/0.5 A/g). In addition, an asymmetric capacitive device composed of the CCN/VO nanostructure and activated carbon is fabricated. It exhibits a remarkable energy density of 96.6 Wh/kg at 811.0 W/kg in the voltage frame of 1.5 V, along with a remarkable cycling stability of 90.2% over 5000 cycles. Moreover, the CCN/VO nanostructure electrode is used to reproduce experimental cyclic voltammetry curves in a numerical simulation model. The unique CCN/VO with a 2D/1D nanostructure exhibits superior electrochemical capacitor characteristics. This result could inspire novel nanostructured electrode materials that can potentially be used in high-performance supercapacitor applications. Graphical abstract: Image 1 Highlights: Cetyltrimethylammonium bromide (CTAB) induced mesoporous g-C3 N4 nanosheet (CN) coupled with V2 O5 nanobelts networks via hydrothermal approach. CTAB-modified pore-rich g-C3 N4 nanosheet (CCN)/VO nanostructure employed for coin-cell-type asymmetric supercapacitor device fabrication. Three electrode CCN/VO nanostructure possesses superior electrochemical activity (192.3 mAh g −1 at 0.5 A g −1 ). CCN/VO nanostructure device exhibited energy density 96.6 Wh kg −1 at a 811.0 W kg −1 power density. Red LED lighted over 17 min with CCN/VO nanostructure device.